Antifungal efficacy of neem leaves (Azadirachta indica) and mahagony fruit bark (Swietenia mahagoni) extracts on leather shoes - Mamun, Md Abdulla Al; Hasan, R; Ahmed, Md R; Paul, AC; Raha, RK (Bangladesh Journal of Scientific and Industrial Research, 2019)
The natural fungicide has been successfully extracted from neem (Azadirachta indica) leaves and mahagony (Swietenia Mahagoni) fruit bark by a solvent extraction method. The antifungal efficacy was evaluated by the application of extract to the fungal-killing on cultured-fungus in Petri-plate and shoes. The fungus was isolated from the shoe and cultured in Sabouraud Dextrose Agar (SDA) plate of 100 mm size petri dish. Different dosing of neem and mahagony extract was applied on the fungus culture and measured the area of fungus killing as an antifungal efficacy of the extracts by “Leaf Area Counter” software. The maximum fungus killing efficacy was optimized. The optimum dosing of neem leaves and mahagony bark extracts were found 0.6 gm/5ml and 0.8 gm/5ml, respectively. After that, the optimum doses of natural fungicide were mixed with commercial shoe shiner and cultured the fungus in SDA plate with and without fungicides. Fungicides containing shoe shiner was an inhibitor to grow the fungus, whereas fungus was grown in fungicides-free shoe shiner within three days. We observed the fungicides-containing shoe-shiner treated dish for a period of one month and found that there was no fungus growth at all. The present findings indicated the possible use of neem and mahagony fruits-bark extract as a natural antifungal agent against post-harvest fungal infestation of shoe commodities and prevented the fungus contamination. Bangladesh J. Sci. Ind. Res.54(3), 257-262, 2019